International techonology competencies perceived by Technicaland Vocational Education and Training (TVET) student in Malaysia - Lam, Kim Wai; Hassan, Aminuddin (Human Resource Management Academic Research Society, 2018)
This study examines the development of an instrument to investigate the educational needs of Malaysian students undergoing technical education and vocational training (TVET), their perception of the importance and relevance of TVET in Malaysia, as well as the factors that contribute to instruction competencies required to enhance the knowledge and reasoning skills of TVET students. A framework model is presented with the aim of revising and further developing curriculum competencies in TVET education based on reviews of the philosophies and learning theories from past studies, and in particular, the Analysis, Design, Develop, Implement, Evaluate (ADDIE) instructional design model. It is proposed that by extending the ADDIE instructional design model to include three learning theories, namely the behaviourist, cognitive, and constructivist theories, a sustainable program can be developed that focuses on assessing the reasoning skills of TVET students. The instruction competencies derived from this revision could enhance the employability of TVET graduates.